Sagot :
1. Find ( f + g ) ( x )
( f + g ) ( x ) = (x + 5) + (2x – 1)
= x + 5 + 2x – 1
= 3x + 4
2. Find ( f – g ) ( x )
( f – g ) ( x ) = f ( x ) – g ( x )
= ( x + 5 ) – ( 2x – 1 )
= x + 5 – 2x + 1
= – x + 6
3. Find ( f • g ) ( x )
( f • g ) ( x ) = f ( x ) • g ( x )
= ( x + 5 ) ( 2x – 1 )
= 2x² – x + 10x – 5
= 2x² + 9x – 5
4. Find ( h/ g ) ( x )
[tex] \frac{h}{g}(x) \: = \: \frac{h(x)}{g(x)} [/tex]
[tex] \frac{2 {x}^{2} + 9y - 51 }{2x - 1} \\ \\ 2x - 1 = 0 \\ \\ 2x = 1 \\ \\ x = \frac{1}{2} \: or \: 0.5[/tex]
5. Find ( f + g ) ( 3 )
Solution
- Step 1. Find ( f + g ) ( x )
( f + g ) ( x ) = (x + 5) + (2x – 1)
= x + 5 + 2x – 1
= 3x + 4
- Step 2. Find ( f + g ) ( 3 )
( f + g ) ( x ) = 3x + 4
( f + g ) ( 3 ) = 3( 3 ) + 4
= 9 + 4
= 13
: Hope this helps. Pa-Brainliest, thanks!
: ᜉᜇᜌᜓᜈ᜔!